The VANDELS survey: dust attenuation in star-forming galaxies at z = 3-4. Issue 3 (22nd February 2018) - Cullen, F; McLure, R J; Khochfar, S; Dunlop, J S; Dalla Vecchia, C; Carnall, A C; Bourne, N; Castellano, M; Cimatti, A; Cirasuolo, M; Elbaz, D; Fynbo, J P U; et al.
Abstract: We present the results of a new study of dust attenuation at redshifts 3 <  z  < 4 based on a sample of 236 star-forming galaxies from the VANDELS spectroscopic survey. Motivated by results from the First Billion Years (FiBY) simulation project, we argue that the intrinsic spectral energy distributions (SEDs) of star-forming galaxies at these redshifts have a self-similar shape across the mass range 8.2 ≤ log (M⋆ /M⊙ ) ≤ 10.6 probed by our sample. Using FiBY data, we construct a set of intrinsic SED templates which incorporate both detailed star formation and chemical abundance histories, and a variety of stellar population synthesis (SPS) model assumptions. With this set of intrinsic SEDs, we present a novel approach for directly recovering the shape and normalization of the dust attenuation curve. We find, across all of the intrinsic templates considered, that the average attenuation curve for star-forming galaxies at z ≃ 3.5 is similar in shape to the commonly adopted Calzetti starburst law, with an average total-to-selective attenuation ratio of RV  = 4.18 ± 0.29. In contrast, we find that an average attenuation curve as steep as the SMC extinction law is strongly disfavoured. We show that the optical attenuation ( AV ) versus stellar mass ( M ⋆ ) relation predicted using our method is consistent with recent ALMA observations of galaxies at 2 <  z  < 3 in the Hubble Ultra Deep Field (HUDF), as well as empirical AV  −  M ⋆ relations predicted by a Calzetti-like law. In fact, our results, combined with other literature data, suggest that the AV – M ⋆ relation does not evolve over the redshift range 0 <  z  < 5, at least for galaxies with log( M ⋆ /M⊙ ) ≳ 9.5. Finally, we present tentative evidence which suggests that the attenuation curve may become steeper at lower masses log( M ⋆ /M⊙ ) ≲ 9.0.